Determination of Serum 25-Hydroxyvitamin D Levels in Patients with Alopecia Areata - Singh Basukala, Manisha; Jha, Ayush; Dawadi, Roji; Shrestha, Rima (Journal of Nepal Health Research Council, 2023)
Background: Alopecia Areata is a common non scarring alopecia with autoimmune etiology. In several previous studies, an insufficient level of 25 hydroxyvitamin D had been correlated with various autoimmune diseases. The current study aimed to determine the level of serum 25 hydroxyvitamin D in patients with alopecia areata. Methods: A cross-sectional study was conducted on 35 patients with alopecia areata who visited the outpatient department of Dermatology of KIST Medical College and Teaching Hospital, Nepal. A prior approval of the institute review committee was taken. Convenience sampling technique period for 3 months (March 2022-May 2022) was used to include the participants (informed consent was taken; in minors parental consent was prepared). The serum levels of 25 hydroxyvitamin D was estimated using Abbott Architect i1000 SR analyser. Result: In this study, Alopecia Areata was common in the age group of 16–30 years (Mean age: 31.65 ± 11.92 Years). The average duration of the disease in Alopecia Areata patients was close to 1 year. This study indicated a lower concentration of 25 hydroxyvitamin D in half of the studied AA patients (51.4%).The number of patches, Severity of Alopecia Tool scoring, serum 25 hydroxyvitamin D level, and age were found to be statistically insignificant with the disease activity. However, a significant positive correlation was found between the Severity of Alopecia Tool score and the number of patches. Conclusions: Although low levels of serum 25 hydroxyvitamin D may be seen among subjects with alopecia areata; No statistical correlation was observed. Hence, a larger study of similar nature is needed in the future to elucidate the exact correlation. Keywords: Alopecia areata; autoimmune; 25 hydroxyvitamin d.